Validation and Development of UV spectroscopy method for the Estimation of Diclofenac sodium in Bulk and dos protected mode interface - Mohammed R . Abdul - Azeez ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
There are presently four direct, speedy, delicate, and exact UV spectroscopic methods accessible for assessing how much diclofenac sodium in drug dosage forms and bulk. A clear UV spectroscopic strategy was made and confirmed to gauge the centralization of Diclofenac sodium utilizing a 20:40 dissolvable combination of acetonitrile and ethanol. Diclofenac sodium was found to have a linearity scope of 2-12 µ g/ml with a location frequency of 276 nm. The ICH rules were utilized to approve the methodology. It is not difficult to utilize, delicate, trustworthy, and produces repeatable outcomes. so supportive for the ordinary assessment of diclofenac sodium.